2013
DOI: 10.1074/jbc.m113.475863
|View full text |Cite
|
Sign up to set email alerts
|

Agonist-dependent Signaling by Group I Metabotropic Glutamate Receptors Is Regulated by Association with Lipid Domains

Abstract: Background: Lipid rafts regulate GPCR signaling. Results: MGluR1 recruitment to lipid rafts is facilitated by a cholesterol recognition/interaction amino acid consensus motif and enhances agonist-dependent signaling. Conclusion: Cholesterol within lipid rafts functions as an allosteric modulator of mGluR1 activity. Significance: Cholesterol altering drugs may provide a means to modulate mGluR activity in neuropsychiatric conditions, including fragile X syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 80 publications
(108 reference statements)
2
43
1
Order By: Relevance
“…At any rate, our data are consistent with a study which showed that ATP-induced Ca 2+ increases originated in specific areas of the caveolin-enriched plasma membrane in endothelial cells, suggesting that caveolin may be involved in the initiation of agonist-stimulated Ca 2+ signaling [44]. However, another report suggests that the interaction of mGlu1 receptor and caveolin-1 is not required for its localization to lipid rafts [40]. It showed that mGlu1 receptor mutated with two caveolin-1 binding sites displayed comparable agonist binding affinity and agonist-induced localization to lipid rafts with wild-type.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…At any rate, our data are consistent with a study which showed that ATP-induced Ca 2+ increases originated in specific areas of the caveolin-enriched plasma membrane in endothelial cells, suggesting that caveolin may be involved in the initiation of agonist-stimulated Ca 2+ signaling [44]. However, another report suggests that the interaction of mGlu1 receptor and caveolin-1 is not required for its localization to lipid rafts [40]. It showed that mGlu1 receptor mutated with two caveolin-1 binding sites displayed comparable agonist binding affinity and agonist-induced localization to lipid rafts with wild-type.…”
Section: Discussionsupporting
confidence: 91%
“…It is also possible that differences of agonist binding affinity according to differential lipid raft localization might regulate the coupling of the receptor signaling. Another recent study suggests that mGlu1α is recruited by agonist to lipid rafts and this is supported in part by intact cholesterol recognition/interaction amino acid consensus (CRAC) motif [40]. The data are in line with our result which showed impairment of Ca 2+ signaling by cholesterol extracting drug, mβCD, implying the importance of cholesterol in the receptor function.…”
Section: Discussionsupporting
confidence: 90%
“…Lipids are integral to the structure of the Kv1.2 potassium channel (Long et al, 2007). Metabotropic glutamate receptors are modulated by cholesterol (Kumari et al, 2013), and many ion channels are affected by phosphatidylinositol 4,5-biphosphate (PIP 2 ; Poveda et al, 2014). Phosphatidylinositol 3,4,5triphosphate (PIP 3 ) is localized to membrane rafts (Hansen, 2015) and maintains -amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor clustering (Arendt et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Flotillin-1 is abundantly expressed in the brain and its selective association with raft membranes has been extensively characterized in both primary neurons and brain tissue [ 56 ] and thus represents a reliable marker of lipid raft enrichment. In contrast, TfR1 is excluded from lipid raft membranes under resting or stimulated conditions [ 57 ] in both primary cells and native tissue and thus affords a reliable indicator of non-raft membranes. We found Flotillin-1 to be consistently enriched in three buoyant gradient fractions (fractions 3 to 5; Fig 1A ) in both mutant and wild type mouse brain whereas TfR1 appeared concentrated in heavy gradient fractions and virtually absent from buoyant, lipid raft enriched membranes ( Fig 1B ).…”
Section: Resultsmentioning
confidence: 99%